Pengaturan Hubungan Menyimpang di Luar Perkawinan bagi Lesbian Dan Gay dalam Perspektif Hukum Hindu - I Kadek Grendy Bhineka; I Nyoman Putu Budiartha; Ni Made Puspautari Ujianti (Warmadewa Press, 2021)
Marriage is a physical and mental bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on the One Godhead. Humans were created to pair men with women in order to continue the lineage, but there are a group of people who behave like the same sex and want to legalize their actions up to the level of marriage through the laws in force in their country. This of course cannot be accepted by some people who contradict same-sex marriage behavior which is commonly referred to as Lesbian, Gay, Bisexual and Transgender, hereinafter referred to as LGBT. This study aims to explain the arrangement of deviant relationships outside of marriage for LGBT people in the perspective of Hindu law. The second one describes the religious perspective in dealing with LGBT perpetrators. This research is designed to use normative legal research with a juridical approach through the hermenutic method. The data used are secondary and primary data which are analyzed qualitatively. The results show Hinduism, there is no single verse or ceremony which legalizes that gay and lesbi can have a marriage or relationship, meaning that it is not allowed to marry, especially with a sacred ceremony, Vedic mantra puja, the second one should not isolate or discriminate but provide education to treat Humanly, gay and lesbian perpetrators must provide protection or educate the perpetrator whether he is accommodated in a place and then given direction or counseling so that the perpetrator is aware of LGBT behavior.